Professional conceptualisation and accomplishment of patient safety in mental healthcare: an ethnographic approach - Braithwaite Jeffrey; Nugus Peter; Travaglia Joanne; Plumb Jennifer (BMC, 2011)
Abstract Background This study seeks to broaden current understandings of what patient safety means in mental healthcare and how it is accomplished. We propose a qualitative observational study of how safety is produced or not produced in the complex context of everyday professional mental health practice. Such an approach intentionally contrasts with much patient safety research which assumes that safety is achieved and improved through top-down policy directives. We seek instead to understand and articulate the connections and dynamic interactions between people, materials, and organisational, legal, moral, professional and historical safety imperatives as they come together at particular times and places to perform safe or unsafe practice. As such we advocate an understanding of patient safety 'from the ground up'. Methods/Design The proposed project employs a six-phase data collection framework in two mental health settings: an inpatient unit and a community team. The first four phases comprise multiple modes of focussed, unobtrusive observation of professionals at work, to enable us to trace the conceptualisation and enactment of safety as revealed in dialogue and narrative, use of artefacts and space, bodily activity and patterns of movement, and in the accomplishment of specific work tasks. An interview phase and a social network analysis phase will subsequently be conducted to offer comparative perspectives on the observational data. This multi-modal and holistic approach to studying patient safety will complement existing research, which is dominated by instrumentalist approaches to discovering factors contributing to error, or developing interventions to prevent or manage adverse events. Discussion This ethnographic research framework, informed by the principles of practice theories and in particular actor-network ideas, provides a tool to aid the understanding of patient safety in mental healthcare. The approach is novel in that it seeks to articulate an 'anatomy of patient safety' as it actually occurs, in terms of the networks of elements coalescing to enable the conceptual and material performance of safety in mental health settings. By looking at how patient safety happens or does not happen, this study will enable us to better understand how we might in future productively tackle its improvement.